Mild regiospecific alcoholysis and aminolysis of epoxides catalyzed by zirconium(IV) oxynitrate - Shinde, Sandip S.; Said, Madhukar S.; Surwase, Trupti B.; Kumar, Pradeep (Tetrahedron Letters, 2015)
A regiospecific method for the ring-opening reaction of epoxides by the primary, secondary, tertiary alcohols, and aryl, aliphatic amines has been developed using non-toxic metal nitrate salt as a catalyst. The best results were obtained using zirconium(IV) oxynitrate among the various screened metal nitrate salts. The reported protocol works efficiently for styrene epoxide and aliphatic as well. (C) 2015 Elsevier Ltd. All rights reserved.
Keywords: Alcoholysis; Aminolysis; Epoxide; Lewis acid; Zirconia

Mechanistic study of nucleophilic fluorination promoted by tri-tert-butanolamine - Lee, Sung-Sik; Jung, Hyun-Kyung; Shinde, Sandip S.; Lee, Sungyul (Journal of Fluorine Chemistry, 2017)
Quantum chemical study is carried out to elucidate the mechanism of S(N)2 fluorination using. CsF promoted by tri-tert-butanolamines. Focus is on the role of the hydroxyl (OH) and the amine functional groups for accelerating the reaction. Our systematic analysis indicates that the OH groups form strong interactions with the nucleophile F-. Thus, it seems that hydrogen bonding with the nucleophile may accelerate the S(N)2 processes rather than retard them, as conventional wisdom suggests. The origin of the experimentally observed improvement of the promotor efficiency in t-butanol solvent over that in CH3CN is examined. We show that the coordination of the solvent t-butanol molecule as Lewis base on the counter-cation Cs+ lowers the Gibbs free energy of activation. (C) 2017 Elsevier B.V. All rights reserved.

Molybdenum oxide-mediated facile aliphatic nucleophilic fluorination - Said, Madhukar S.; Khandare, Leena; Shinde, Sandip S. (Tetrahedron Letters, 2017)

Metabolic engineering and synthetic biology for isoprenoid production in Escherichia coli and Saccharomyces cerevisiae - Navale, Govinda R.; Dharne, Mahesh S.; Shinde, Sandip S. (Applied Microbiology and Biotechnology, 2021)
Isoprenoids, often called terpenoids, are the most abundant and highly diverse family of natural organic compounds. In plants, they play a distinct role in the form of photosynthetic pigments, hormones, electron carrier, structural components of membrane, and defence. Many isoprenoids have useful applications in the pharmaceutical, nutraceutical, and chemical industries. They are synthesized by various isoprenoid synthase enzymes by several consecutive steps. Recent advancement in metabolic engineering and synthetic biology has enabled the production of these isoprenoids in the heterologous host systems like Escherichia coli and Saccharomyces cerevisiae. Both heterologous systems have been engineered for large-scale production of value-added isoprenoids. This review article will provide the detailed description of various approaches used for engineering of methyl-d-erythritol-4-phosphate (MEP) and mevalonate (MVA) pathway for synthesizing isoprene units (C-5) and ultimate production of diverse isoprenoids. The review particularly highlighted the efforts taken for the production of C-5-C-20 isoprenoids by metabolic engineering techniques in E. coli and S. cerevisiae over a decade. The challenges and strategies are also discussed in detail for scale-up and engineering of isoprenoids in the heterologous host systems.
Keywords: Escherichia coli; Isoprenoids; Metabolic engineering; Saccharomyces cerevisiae; synthetic biology